Amlodipine overdose - A case report - Ananth Rupesh, Kattamreddy; Taqiuddin Khan, M (Journal of Indian Academy of Forensic Medicine, 2019)
An autopsy surgeon encounters different types of toxicological deaths in practice which include suicidal consumption of poisons, accidental consumption of poisons and homicidal administration of poisons. Kenneth Barlow insulin murder case is a classic case of homicidal poisoning reported in history. A recent incident in 1990 involving death of 84 Nigerian children after being given "My Pikin", teething syrup contaminated with diethylene glycol is one of the fatal episodes of accidental toxicological deaths. Suicide by poisoning forms a part of our routine practice in India. However, suicide by therapeutic drug abuse is a rather uncommon phenomenon.. The commonly encountered therapeutic drug abuse cases involve NSAIDs, purgatives, steroids, etc. We report a case of amlodipine toxicity causing death with due emphasis towards autopsy findings, toxicokinetics, drug interactions, analytical toxicology considerations and differential diagnosis of capillary leak syndrome.